Condition hair as an indicator of environmental contamination by heavy metals - Пшегалінська, Л.В.; Білик, Т.І. (Proceedings of National Aviation University (archive), 2009)
By data of authors it is observed the correlation between the content of hard metals in hair and the statistics of population, and also lagging in mental abilities of children. The explorations were provided with samples of hair of students which were refered to the first group of risk. From the provided experiment was established the average content of plumbum is 10,32 mkg/g, it corresponds on the data established for people who live on relative non-polluted territory.